Information needs of the public health workforce in 2015 (Journal of EAHIL, 2016)
This research investigates the information needs of the public health workforce in 2015. It builds on previousresearch to look at information access, information use, information skills and barriers to information. Two online surveys were created and disseminated gathering both qualitative and quantitative data. Results showed that there are various uses for information. Respondents felt confident in their literature search skills but less confident in managing bibliographic references and critical appraisal. There were common barriers to information including lack of time and financial restrictions. The results from this information needs assessment support findings from previous research. Further research should explore ways to overcome barriers to information and get a better understanding of individual sector needs and barriers to information.